PESAN DAKWAH DALAM KITAB TA’LIMUL MUTA’ALIM KARYA SYEIKH AL-ZARNUJI - Dwi Astuti; Abdi Fauji Hadiono (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2025)
is an obligation for all Muslims. One way to preach is through written works such as books or scriptures. One of them is the Book of Ta'limul Muta'alim by Sheikh al-Zarnuji. Where we can understand knowledge about human nature in this book. Based on the background above, this research will answer the problem: What is the message of da'wah in the book Ta'limul Muta'alim by Sheikh Al-Zarnuji? What is the material contained in the book Ta'limul Muta'alim by Sheikh Al-Zarnuji? The method used in this research is a qualitative research method with content analysis techniques which are widely used to study da'wah messages. This research analyzes the da'wah message in each paragraph in certain selected chapters using observation techniques. The results of this research show that from the book "Ta'limul Muta'alim" there are many da'wah messages, namely those related to the aqidah message, sharia messages, and moral messages related to current life. Furthermore, the most dominant da'wah message in the book "Ta'limul Muta'alim" is the aqidah message, followed by the moral message and finally the sharia message